การพัฒนาระบบการพยาบาลเพื่อป้องกันและควบคุมการติดเชื้อระบบ ทางเดินปัสสาวะในผู้ป่วยที่ได้รับการใส่คาสายสวนปัสสาวะ Development System of Nursing for Infection Control in Foley’s Catheter Patient - ชวนไชยสิทธิ์, กาญจนา; สสัสติวัดษ์, กิตติรัตน์; ชัยบุตร, ศันสนีย์ (วารสารการพยาบาลและการดูแลสุขภาพ, 2018)
This Participatory Action Research aimed to develop a nursing system for catheter-associated urinary tract infection (CAUTI) control and prevention and evaluate its effects on CAUTI incidence and nursing quality indicators in Chaiyaphum Hospital. Kemmis & McTaggart participatory action research model was adopted as the study framework. Participants included the hospital nurse director, 38 head nurses, 110 registered nurses and all patients who had indwelling urinary catheters during the study period. Research instruments included the CAUTI clinical nursing practice guideline (CNPG, demographic form, nurse’s adherence to the CAUTI CNPG observation form, CAUTI surveillance form, and nosocomial infection control and prevention quality appraisal form. The study was conducted in 2 cycles with 4 phases in each cycle including 1) situational analysis of CAUTI incidence, quality of nosocomial infection control and prevention and outcomes of the CNPG implementation, 2) planning, 3) implementation, and 4) outcome evaluation. The first cycle was undertaken to develop a nursing system for CAUTI control and prevention and CAUTI CNPG and implemented the system to rest its feasibility and effects on CAUTI reduction. The second cycle was carried out to implement the nursing system to prevent CAUTI in all hospital departments during October 2016 and September 2017. Content analysis was used to analyze qualitative data. Descriptive statistics, frequencies, means, and percentage were used to analyze quantitative information. Results revealed that 1) the nursing system for CAUTI control and prevention was feasible to be used in all hospital departments, 2) the nursing care quality for nosocomial infection control and prevention was rated at 2.81, 3) CAUTI incidence decreased to 1.07/1000 catheter-day with the highest incidence at the surgical wards, and 4) nurses’ adherence to the CAUTI CNPG was averaged at 87.2%.